CDBA-based sinusoidal quadrature oscillator with current controlled amplitude - Prasertsom, Danucha; Tangsrirat, Worapong (My University, 2010)
This paper describes a sinusoidal quadrature oscillator circuit using current differencing buffered amplifiers (CDBAs), that features a single-resistance-controlled frequency and current amplitude control. The proposed circuit contains two CDBAs, three resistors, and two grounded capacitors. The oscillation condition (OC) and the oscillation frequency (ω0) of the circuit are independently controlled by a single resistor, whereas the oscillation amplitude is electronically controlled by an external DC current. Outputs of two sinusoidal voltages are shifted by 90°. The validity of the proposed circuit has been verified by hardware circuit tests using AD844 based CDBA. ©2010 IEEE.